PELATIHAN PENULISAN PROPOSAL SKRIPSI UNTUK MAHASISWA FKIP UNBARA (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
Abstract This PKM activity originated from the interest of the lecturers in the Indonesian Language and Literature Education Study Program, Unbara, so that the writing of proposals and reports for lecturers and students in SouthSumatra, OKU Baturaja district, was in accordance with the rules of the Ministry. This form of PKM is a training withthe title "Thesis Proposal Writing Training for Students in the Indonesian Language and Literature Education StudyProgram Unbara This training was attended by 40 people consisting of final semester students in the UnbaraIndonesian Language and Literature Education Study Program This training was attended by 40 people consisting offinal semester students at the Unbara Indonesian Language and Literature Education Study Program. )Implementation: carrying out training, analyzing test results, and assisting in the preparation and preparation ofscientific article publications, holding workshops in class; ) 3) End: Making proposals and scientific reports producesproposals and scientific work reports.The result of this PKM is the implementation of the Proposal Writing Trainingand Scientific Reports for Students according to the steps that have been set and the proposals and scientific reportsof PBSI Unbara students.